Predictors of late virologic failure after initial successful suppression of HIV replication on efavirenz-based antiretroviral therapy - Isaac Singini (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Background: Practical issues, including cost, hinder implementing virologic monitoring of patients on antiretroviral therapy (ART) in resource-limited settings. We evaluated factors that might guide monitoring frequency and efforts to prevent treatment failure after initial virologic suppression. Methods: Participants were the 911 HIV-infected antiretroviral-naïve adults with CD4 count <300 cells/μL who started efavirenz-based ART in the international A5175/PEARLS trial and achieved HIV-1 RNA <1000 copies/mL at 24 weeks. Participant report of ART adherence was evaluated using a structured questionnaire in monthly interviews. Adherence and readily available clinical and laboratory measures were evaluated as predictors of late virologic failure (late VF: confirmed HIV-1 RNA ≥1000 copies/mL after 24 weeks). Results: During median follow-up of 3.5 years, 82/911 participants (9%) experienced late VF. Of 516 participants reporting missed doses during the first 24 weeks of ART, 55 (11%) experienced late VF, compared with 27 (7%) of 395 participants reporting no missed doses (hazard ratio: 1.73; 95% CI: 1.08, 2.73). This difference persisted in multivariable analysis, in which lower pre-ART hemoglobin and absence of Grade ≥3 laboratory results prior to week 24 were also associated with higher risk of late VF. Discussion: In this clinical trial, the late VF rate after successful suppression was very low. If achievable in routine clinical practice, virologic monitoring involving infrequent (e.g. annual) measurements might be considered; the implications of this for development of resistance need evaluating. Patients reporting missed doses early after ART initiation, despite achieving initial suppression, might require more frequent measurement and/or strategies for promoting adherence.